Atención al usuario en el Seguro Social Campesino del Recinto Huilloloma Provincia de Bolívar - Heredia Paguay, Mayra Jacqueline (2021)
The investigative study carried out at the Peasant Social Security Dispensary of the Huilloloma campus, an institution in charge of providing first-rate medical care to vulnerable populations, which aimed to evaluate user care due to the fact that there are problems in the satisfaction of members. The technique used consisted of descriptive research that will include describing the information of the event studied with the application of a qualitative approach. The techniques applied were the survey and direct observation with their respective collection instruments, the first aimed at the users of the dispensary and the second at the facilities of the dispensary. The results obtained were that the service perceived by the users of the dispensary is regular, which is why they indicated that they have little confidence in the knowledge of the doctors and nurses and the poor attention to the user is due to inconveniences in scheduling appointments as the time to be served.